Efficacy of riprap design for protection of quay structures against propeller-induced scouring - Tan, Qin Xiang (Nanyang Technological University, 2021)
Modern-day vessels can cause severe scouring around quay structures during berthing and unberthing manoeuvres. The scouring of sediment bed near the toe of quay structures might subsequently result in instability of the quay structure. As such, it is imperative to deploy properly designed bed protection along quay structures. To that end, PIANC WG180:“Guidelines for Protecting Berthing Structures from Scour Caused by Ships” provides comprehensive guidelines to design various types of scour protection around quay structures. This study examined the efficacy of the deterministic design procedures for designing riprap bed protection along closed quay structure. Rock stability tests were conducted to determine the critical efflux velocity of the propeller jet when shear failure of the riprap was observed. The critical efflux velocity measured from the experiments were subsequently compared with the critical efflux velocity predicted using the German and Dutch methods. In total, five different median rock sizes and five different wall clearances were tested in this study. The experimental results show that the Dutch method is overconservative for all 24 test conditions, while the German method produces under-designed riprap for test conditions with large wall clearance. In general, it was observed that the factor of safety for riprap bed protection designed with the German and Dutch methods have a positive correlation with the median rock size of the riprap, and a negative correlation with the horizontal wall clearance. Through regression analysis, this study proposed two sets of empirical equations to estimate the factor of safety for the German and Dutch methods. Based on the experimental data, an empirical equation to estimate the required median rock size for riprap bed protection was also proposed. Additionally, this study also investigated the scour formation on gravel bed, where the propeller jet was confined by a perpendicular quay structure. Key parameters such as efflux velocity, rock size, vertical propeller clearance and horizontal wall clearance were tested to understand their influence on the formation of scour hole. Based on the experimental data, an empirical equation was proposed to estimate the maximum asymptotic scour depth on the gravel bed for a given flow condition. This empirical equation can be used to determine if localized failure of riprap will occur for the critical flow condition, and it can also help engineers to identify the appropriate riprap layer thickness.